You never heard of Casey Stengel?! - Winter, Jonah, 1962- (Schwartz & Wade Books, 2016)
Looks at the life and career of Casey Stengel, from his days as a player on the Brooklyn Dodgers to his string of pennants and World Series wins as manager of the New York Yankees.